Cooperative dual-arm control for heavy object manipulation based on hierarchical quadratic programming - Dio, Maximilian; Völz, Andreas; Graichen, Knut (2023 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS), 2023)

Safe active learning and probabilistic design of experiment for autonomous hydraulic excavators - Dio, Maximilian; Demir, Ozan; Trachte, Adrian; Graichen, Knut (2023 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS), 2023)

Time-Optimal Path Parameterization for Cooperative Multi-Arm Robotic Systems with Third-Order Constraints - Dio, Maximilian; Graichen, Knut; Völz, Andreas (2024 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS), 2024)
This paper presents a time-optimal path parameterization (TOPP) method for cooperative multi-arm robotic systems (MARS) manipulating heavy objects with third-order constraints that include jerk, torque rate and wrench rate limits. The method is based on a problem reformulation as a sequential linear program and provides a unified planning approach that is faster than previous convex optimization techniques. The equivalence to a reachability-based TOPP is shown and simulation results for a cooperative MARS consisting of two 7 degree of freedom (DOF) robots and a tightly grasped object with 6 DOFs are provided.
CRIS-Team Scopus Importer:2025-04-01

Time-Optimal Path Parameterization with Viscous Friction and Jerk Constraints based on Reachability Analysis - Dio, Maximilian; Wahrburg, Arne; Enayati, Nima; Graichen, Knut; Völz, Andreas (Proceedings 2025 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS), 2025)